ANALISIS PELAKSANAAN SIRKUMSISI PADA BAYI PEREMPUAN PARAMEDIS RSUD ARIFIN ACHMAD PROVINSI RIAU - LPPM Al-Insyirah (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2016)
Female Genital Mutilation (FGM) or circumcision is any procedure / action which is intended to eliminate most or all of the external female genital organs on the grounds of culture, custom, religion or on the grounds of hygiene. Circumcision in women has a negative impact on women's reproductive health as a tendency to bleeding, obstruction when having sexual intercourse, Cause urinary tract infections, cysts and abscesses, Colloids, damage to the urethra resulting in dispareni, sexual dysfunction, and cronic morbidity. Female circumcision is seen as gender issues which women lost the right to keep the continuity of reproductive function. Female circumcision is a culture-based violence that cause women to experience physical trauma, Psychic and sexual. several reasons for FGM, namely: cultural reasons, Gender identity, Controlling women's sexuality and reproductive functions, and reasons of hygiene, health, as well as beauty. This research is descriptive qualitative to get information about the reason for paramedics Arifin Achmad Pekanbaru still carry out circumcision on baby girls Year 2015. The location of this research conducted at Arifin Achmad Pekanbaru . This study was conducted in May and June 2015. Data analysis using analytical consent. The results showed that the practice of female circumcision among paramedics who work at Arifin Achmad Riau Province is still going on until now even though they are already aware of the prohibition of the medicalization of the practice of female circumcision , because it is a religious and culture. Paramedics should need to have an understanding and knowledge of the good and true based on logic and science of female circumcision and complications that can occur as a result of female circumcision.